New species and records of the genus Aegla Leach, 1820 (Crustacea, Anomura, Aeglidae) from the West-Central region of Rio Grande do Sul, Brazil - Santos,Sandro (2013)
Aeglidae are anomuran freshwater "crabs" found only in southern South America. In Brazil, the greatest species diversity occurs in hydrographic basins of the state of Rio Grande do Sul. Two new species, Aegla georginae and Aegla ludwigi, are described from the Ibicuí and Ijuí Rivers, respectively (Uruguay River Basin). The new taxa can be distinguished from other Aegla species based on both morphological and molecular characters. The two new species have a very restricted distribution and are categorized as endangered (A. georginae) and critically endangered (A. ludwigi) using IUCN Red List criteria. We also summarize and present new records of the Aegla species occurring in the Uruguay River Basin.